Screening of transovarial denv transmission in field—collected Aedes albopictus in Pangsapuri Damai and Subang Bestari, Selangor / Nurul Adilah Amrannudin - Amrannudin, Nurul Adilah (2015)
Dengue is currently the most significant arboviral infection afflicting communities in Malaysia. Recent multiple outbreak cycles of dengue cases with expansion of hotspot areas has raised public concerns. These incidences may be due to inherent maintenance of DENV harboured by an invasive vector, Aedes albopictus through transovarial transmission in nature. Despite of this etiological phenomenon, less attention has been paid on virological surveillance by detecting DENV from mosquito vectors population as an early warning surveillance system for forestalling of impending outbreak. Hence, the present study was conducted to detect the natural transovarial DENV transmission in Aedes albopictus population during outbreak seasons. Two dengue infested areas in the Shah Alam Municipality have been chosen in this study. Field-collected eggs were trapped in Pangsapuri Damai (U4) and Subang Bestari (U5), Shah Alam and reared until adulthood under insectary conditions. Prior to obtain substantial detection of pure DENV RNA template from pooled Aedes albopictus, optimization of viral extraction method using various kits and protocols was performed use USM laboratory strain, Aedes albopictus F1611. The most optimal viral extraction method was selected and homogenates of 10 female adults Aedes albopictus were used to screen transovarial transmission of DENY using multiplex qRT-PCR. Despite the high sensitivity and specificity of realtime assay, no DENV was detected in all samples that entailed no maintenance of DENY among Aedes albopictus populations in nature of epidemic areas in this research. This finding probably owes to the abundance ofblood meal sources that are insensible for DENV persistence in nature, sample size population, shorter sampling time frame, unsuitable period of vector surveillance and misconception of dominant vectors in collection locality. Thus, the current findings could be improvised in the future to detect transovarial transmission of DENV in nature during inter-epidemic period of re-epidemic areas as a reliable sentinel tool for dengue outbreak.